Preferensi Konsumen Produk Susu Cair dalam Kemasan di Kota Depok - Abdur Rauf (Sharia Agribusiness Journal, 2024)
AbstractThe aim of this research is to determine the characteristics of consumers, examine their preferences for packaged liquid milk products in Depok City, and find out what variables are the main considerations in purchasing these products.The survey method was carried out using a direct questionnaire to 100 selected respondents.The data was then analyzed using descriptive analysis for consumer characteristics and conjoint analysis for product preferences.The research results show that the majority of consumers of packaged liquid milk in Depok City are women aged 21–30 years, most of whom are private employees or students with an income of <Rp. 2,000,000.They tend to buy 3-4 medium-sized packages of liquid milk per month, with the Ultra Milk brand being the main choice.Purchases are generally made at supermarkets/minimarkets or stalls/shops.Based on conjoint analysis, consumer preferences tend to be products with well-known brands, chocolate flavor variations, UHT liquid milk types, nutritional content rich in vitamins and minerals, composition with >50% fresh milk, expiration date >6 months, and prices around Rp. 5,000–10,000.The variables most considered when purchasing are flavor variations, brand, price, type of liquid milk, nutritional content, composition and expiration date.Keywords: consumer preferences; milk; product variables; conjointAbstrak Tujuan penelitian ini adalah untuk mengetahui karakteristik konsumen, mengkaji preferensi mereka terhadap produk susu cair kemasan di Kota Depok, serta mengetahui variabel apa yang menjadi pertimbangan utama dalam pembelian produk tersebut. Metode survei dilakukan dengan kuesioner langsung kepada 100 responden terpilih. Data kemudian dianalisis menggunakan analisis deskriptif untuk karakteristik konsumen dan analisis conjoint untuk preferensi produk. Hasil penelitian menunjukkan bahwa mayoritas konsumen susu cair kemasan di Kota Depok adalah perempuan berusia 21–30 tahun, sebagian besar merupakan karyawan swasta atau pelajar/mahasiswa dengan pendapatan 50%, tanggal kedaluwarsa >6 bulan, dan harga berkisar Rp5.000–10.000. Variabel yang paling dipertimbangkan dalam pembelian adalah variasi rasa, merek, harga, jenis susu cair, kandungan nutrisi, komposisi, dan tanggal kedaluwarsa.Kata kunci: preferensi konsumen; susu; variabel produk; conjoint